Restenosis following percutaneous transluminal angioplasty: clinical, physiologic and pathological features. - Cox, J L (1986)
Percutaneous transluminal coronary angioplasty (PTCA) has been used clinically for 8 years and is becoming widely accepted in the treatment of atherosclerotic coronary artery disease. Since the long-term effects of the procedure are unknown, the rate of restenosis following the procedure, approximately 30%, is of major concern. We briefly review the current status of PTCA and the effect of angioplasty on the vessel wall and discuss proposed mechanisms of recurrent stenosis.